Testosterone fluctuations in response to a democratic election predict partisan attitudes toward the elected leader. (November 2021) - Prasad, Smrithi; Knight, Erik L.; Sarkar, Amar; Welker, Keith M.; Lassetter, Bethany; Mehta, Pranjal H.
Abstract: Intergroup competitions such as democratic elections can intensify intergroup polarization and conflict. Partisan attitudes toward the elected leader can also shift from before to after an election, but the biology underlying these attitudinal shifts remains largely unknown. An important factor could be the hormone testosterone, which is theorized to fluctuate during competition and to influence status seeking. In a naturalistic study of 113 registered voters, we measured changes in testosterone levels and attitudes toward the winner of the 2012 US Presidential Election. We found that supporters of the losing candidate (Mitt Romney) showed acute increases in testosterone levels compared to supporters of the winner (Barack Obama) on the evening of Election Day. Supporters of the losing candidate also demonstrated flatter diurnal testosterone slopes on Election Day that persisted up to two days after the election. Furthermore, greater increases in acute testosterone levels and flatter diurnal slopes among supporters of the losing candidate were associated with less positive evaluations of the winning candidate. These testosterone-moderated attitudinal shifts observed in the days after the election showed a directionally similar pattern with a weaker effect size six months later. Finally, we confirmed that the main results were robust to alternative data analytic choices using multiverse specification curve analysis. The findings from this paper suggest that hormonal responses to large-scale intergroup competitions may shape how we perceive our elected leaders, shedding light on the biology of intergroup relations. Highlights: Supporters of a losing candidate showed increases in testosterone on election night. Supporters of a losing candidate showed flatter diurnal testosterone slopes up to two days after election day. Testosterone changes predicted shifts in attitudes toward the elected leader. Testosterone-moderated attitude shifts lasted up to a few days post-election. Testosterone-moderated attitude shifts were similar but weaker six months later.